1985
DOI: 10.2170/jjphysiol.35.765
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of isoproterenol-stimulated tissue cyclic AMP level by cholinergic agonists in rat parotid gland.

Abstract: It was found that methacholine and carbamylcholine, in addition to their known inhibitory effect, augmented the effect of isoproterenol on tissue cyclic AMP accumulation. The effect of methacholine was dose dependent, and significant augmentation was obtained at 0.1 µM with the maximum being attained at about 0.5 µM, whereas more than 10 , LM were required to obtain the inhibitory effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
3
6
0
Order By: Relevance
“…These results are consistent with our previous observations which showed that norepinephrinestimulated parotid cyclic AMP accumulation is decreased in the presence of phentolamine (YOSHIMuRA et al, 1985). The augmentation induced by phenylephrine was almost completely abolished by omission of calcium in the medium.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are consistent with our previous observations which showed that norepinephrinestimulated parotid cyclic AMP accumulation is decreased in the presence of phentolamine (YOSHIMuRA et al, 1985). The augmentation induced by phenylephrine was almost completely abolished by omission of calcium in the medium.…”
Section: Discussionsupporting
confidence: 93%
“…As reported in our previous paper (YOSHIMURA et al, 1985), the peak level of tissue cyclic AMP was usually attained at about 2 min after the addition of isoproterenol (the shortest time point examined). The tissue cyclic AMP level declined rapidly thereafter and reached a level only about 2-fold greater than the basal one (the level before the addition of isoproterenol).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Protein exocytosis is induced mainly by intracellular cAMP while #uid secretion results from elevation of intracellular free calcium. Intracellular calcium also induces small amounts of amylase secretion (Putney, 1986;Yoshimura & Nezu, 1992). Yoshimura et al developed a perfusion system which shows the velocity of amylase release in 30 s increments (Yoshimura & Nezu, 1991;.…”
Section: Introductionmentioning
confidence: 99%